(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
The research aims to examine the relationship between Iran’s total carpet exports and GDP in the light of changes in the overall price level in the Iranian economy for the duration of the period (2004-2023) Using the standard program (Eviews 9) In order to analyze the relationship between variables, the self-degradation model of distributed deceleration was used (ARDL) The research has reached a range of conclusions, including a long-term balance between total carpet exports and GDP, as it becomes clear to us that Iranian carpet exports contribute positively and morally to Iran’s economic growth during the study period. Short-term analysis also shows a short-term relationship between variables. This research reflects the importance of the carpet sector as an important and central factor in supplying and supporting the economy with diversification and lack of reliance on oil exports in the Iranian economy